A brief discussion about the circulation of North-Italic Firmalampen marks found in Roman Dobrudja (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2024)
Regarding ancient clay lamps, one can only be impressed by the variety and creativity involved in certain types. Out of the numerous types of lamps that have been discovered and catalogued during past centuries, one particular category sparks interest in those who research the activity of this industry, and that is Firmalampen. This paper aims to start a new discussion regarding some aspects around the presence of this special type of lamps in ancient Dobrudja, part of the province of Moesia Inferior, mainly about the circulation of the North-Italic marks in this region, the trade and the local production. By comparison with other parts of the Empire, we can acknowledge some potential regional particularities and preferences of the population towards a widely spread product.